Characteristics and sources of atmospheric volatile organic compounds (VOCs) along the mid-lower Yangtze River in China. (October 2018) - Zhu, Hailin; Wang, Hongli; Jing, Shengao; Wang, Yifan; Cheng, Tiantao; Tao, Shikang; Lou, Shengrong; Qiao, Liping; Li, Li; Chen, Jianmin
Abstract: The Yangtze River Delta (YRD), one of the most important developed urban regions in eastern China, has been experiencing severe air pollution due to the rapid economic development. VOCs characterization and sources were studied based on ship-based measurements along the mid-lower Yangtze River (MLYR). The measured VOCs mean concentration was (65.5 ± 16.8) ppbv, among which alkanes, alkenes, oxygenated VOCs (OVOCs), aromatics and halogenated hydrocarbons (XVOCs) are (26.4 ± 7.2) ppbv, (11.3 ± 3.6) ppbv, (11.3 ± 4.6) ppbv, (6.3 ± 2.6) ppbv, (5.9 ± 2.7) ppbv, and (4.4 ± 1.8) ppbv, respectively. Interestingly, the present result shows much lower aromatics fractions and higher long-lived species fractions than those in YRD's urban and suburban areas, which is similar to those in rural areas, but higher ship emissions-related species fraction than those in rural areas. The positive matrix factorization (PMF) model is used to identify and apportion the possible sources of ambient VOCs along the MLYR. According to source apportionment, the shipping emission takes up (23.5 ± 20.0)% of total VOCs on average. Moreover, the other three sources are also identified for VOCs with somewhat spatial variability, including chemical and petrochemical industries (12.9 ± 9.2%), combustion-related emissions (36.1 ± 17.9%), and regional aged air mass (27.5 ± 16.2%). In general, the VOCs sources in the waterway are very different from those published results over urban and suburban areas in the YRD. The present study highlights that rural VOCs pollution should be paid attentions to, and common differentiated controlling measures are essential to reduce emissions in the whole YRD. Graphical abstract: Image 1 Highlights: VOCs characterization and source along the mid-lower Yangtze River were presented. Ship emissions contributed (23.5 ± 20.0)% to VOCs in YRD region. Different control measures are essential to reduce VOCs in YRD rural and urban.